Economic Profitability Analysis of Rainfed Organic Farming in SW Spain. (June 2014) - Pardo, Gabriel; Perea, Francisco; Martínez, Yolanda; Urbanoa, José María
The economic importance of organic production systems is growing year on year. Producers who wish to convert their farms to organic farming face significant transition costs due to changes in management, work organization and lifestyle. The aim of this study was to compare the yield and economic outputs of a conventional and an organic farming system in south-west Spain, a region characterized by a subhumid climate. The organic rotation of wheat–sunflower–peas–faba bean (green manure) was compared with a conventional rotation of wheat–sunflower over four cropping seasons. Economic analysis showed that organic farming was 62% more profitable, assuming current organic premium prices, and 36% more profitable when selling products in conventional markets. However, without the Common Agricultural Policy and regional payments and with conventional prices, the profitability of organics falls below that of conventional production.